The differences of tooth density changes in the applications of 45% carbamide peroxide PF and 38% hydrogen peroxide PF as dental bleaching agents and after the application of 1.2% acidulated phosphoric fluoride - Jurnalis, Devriza; Natasasmita, Setiawan; Sukartini, Endang (Padjadjaran Journal of Dentistry, 2010)
The changes of tooth density is caused by the dissolutions of mineral enamel (demineralization) by bleaching agent. The purpose of this research was intended to know tooth density changes after the application of bleaching agent using 45% carbamide peroxide potassium fluoride (PF) and 38% hydrogen peroxide potassium fluoride (PF) and after the application of 1.2% acidulated phosphoric fluoride (APF).This research was true experimental in-vitro. Sample taking was by random sampling. The sample consisted of 32 maxillary central incisive permanent teeth. The tooth density was measured using RVG (Radiovisiography). The research results were analyzed and tested in a pair and in a pair of two sample for means using t student method. The conclusion of the research was a decrease of tooth density after the application of bleaching agent with 45% carbamide peroxide PF and 38% hydrogen peroxide PF with statistically significant. After the application of 1.2% APF the density increased significantly but the density was lower than original density. There was no significant difference between bleached with 45% carbamide peroxide potassium fluoride and 38% hydrogen peroxide potassium fluoride.